Plasmonic Mach-Zehnder Interferometers Based on Air-Gap Couplers - Rami A. Wahsheh (IEEE Photonics Journal, 2023)
Mach-Zehnder interferometers (MZIs) are vital in optical biosensor applications and high-density integrated photonic circuits. In this research work, we theoretically investigate the design steps of MZIs, consisting of 3-dB plasmonic splitters sandwiched between two dielectric waveguides with an air-gap coupler at the interface from each side. The proposed MZI designs feature a compact size, ensuring high transmission coupling efficiency without introducing additional radiation or reflection losses, as observed in tapered, T- and Y-shaped splitters. The analytical results and simulations prove that the proposed MZI designs offer a broad spectrum range with a high fabrication tolerance and the ability to use them in all-optical plasmonic circuits.